The Impact of Air Pollution on Atopic Dermatitis. Literature review - Natalia Dolata; Bartosz Balcer; Katarzyna Kuleta (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose The rising level of air pollution is currently a serious worldwide problem. Airborne pollutants, such as PM, O3, CO, NOx, SO₂, and heavy metals, negatively impact the entire body, contributing to the dysfunction of many systems. The aim of this study was to review the literature on the impact of selected air pollutants on the development or exacerbation of atopic dermatitis, and to elucidate the mechanisms responsible for this. Materials and methods The literature available in PubMed and Google Scholar databases was reviewed using the keywords: "air pollution", "atopic dermatitis", "skin lesions". Description of the state of knowledge Available studies have provided information on the significant impact of air pollution on the development and exacerbation of atopic dermatitis. Air pollutants can induce skin changes through various mechanisms, such as damage to the epidermal barrier, disruption of skin microflora, oxidative stress, initiation of inflammatory responses, or activation of the aryl hydrocarbon receptor pathway. Conclusions Reducing air pollution is crucial for improving overall public health and decreasing the incidence of many diseases, including atopic dermatitis. Further research is needed to deepen the understanding of the relationship between air pollution and atopic dermatitis, as well as the mechanisms responsible for it, and to develop effective strategies for protecting the skin from pollutants.